Current Progress and Challenges of Electromagnetic Wave Absorbing Materials at High Temperature - Zhixiao Wang; Tao Yang; Linlin Zhou; Xinmei Hou; Zhi Fang; Yanglong Hou (Advanced Science)
Abstract With the rapid development of science and technology, electromagnetic waves have deeply penetrated various fields. However, they also bring a higher demand for electromagnetic protection. Electromagnetic wave absorbing materials (EMWAMs) can significantly reduce or even eliminate the reflection and scattering of electromagnetic waves by converting electromagnetic wave energy into heat energy and dissipation. In recent years, the research work on EMWAMs mainly focuses on the material systems applied at the normal temperature, and its absorption mechanism is systematically discussed. However, at the elevated temperature, the electromagnetic loss mechanism changes, and the suitable EMWAMs become limited. At the same time, the testing method of EMWAMs at high temperature also remains a challenge. In this work, the electromagnetic loss mechanism and testing methods for high‐temperature EMWAMs, especially above 800 °C, are discussed. Based on this, a selection criterion for EMWAMs at high temperature is proposed.